Cafés in Braunschweig - Albrecht, Peter (Wallstein Verlag, 2026)
A place that is commonplace today, but has changed over time: café culture in and around Braunschweig from the 18th to the 21st century. Today it is taken for granted, but in the past it was a luxury product – a cup of coffee. The drink was accompanied by the emergence of a place of its own. The first cup of coffee was probably drunk in Braunschweig towards the end of the 17th century, but at the beginning of the 18th century, the vast majority of the inhabitants were still unaware of this strange product from the Orient – until the trade fair city got a “large coffee house” in 1714. Peter Albrecht has been studying the history of coffee in and around Braunschweig for decades. Now, using archive sources and newspaper advertisements, he traces the history of café culture on the Oker from its beginnings to the 21st century. The places where it was consumed were as varied as the ways in which the drink could be served: first coffee houses and garden restaurants, then bakeries, “Café-Chantant,” bars, restaurants, and hotels – right up to today's well-known “McCafé.” The author not only examines the chequered history of the various businesses, but also highlights the transformation of the “café” as a cultural and social meeting place: from the demonstrative levelling of class boundaries to a modern venue for a first date.